An Experimental Study on the Thermal Conductivity and Dynamic Viscosity of Tio2-Sio2 Nanofluids in Water: Ethylene Glycol Mixture - M. F., Nabil; Azmi, W. H.; K., Abdul Hamid; R., Mamat; Hagos, F. Y. (Elsevier, 2017)
The hybrid nanofluid has been thriving among researchers due to its potential to improve heat transfer performance. Therefore, various studies on heat transfer properties need to be carried out to provide a better understanding on hybrid nanofluid performance. In this paper, the experimental work is focused on the thermal conductivity and dynamic viscosity of TiO2-SiO2 nanofluids in a mixture of water and ethylene glycol (EG) with volume ratio of 60:40. The stable suspension of TiO2-SiO2 prepared at volume concentrations of 0.5 to 3.0%. The measurements of thermal conductivity and dynamic viscosity were performed at a temperature range of 30 to 80 °C by using KD2 Pro Thermal Properties Analyser and Brookfield LVDV III Ultra Rheometer, respectively. The thermal conductivity of TiO2-SiO2 nanofluids was improved by increasing the volume concentration and temperature with 22.8% maximum enhancement. Besides, the viscosity of TiO2-SiO2 nanofluids showed evidence of being influenced by nanofluid concentration and temperature. Additionally, the TiO2-SiO2 nanofluids behaved as a Newtonian fluid for volume concentration up to 3.0%. The properties enhancement ratio suggested that TiO2-SiO2 nanofluids will aid in heat transfer for concentrations of more than 1.5% and within the range of the temperature studied. A new correlation for thermal conductivity and dynamic viscosity of TiO2-SiO2 nanofluids were developed and found to be precise.